2017
DOI: 10.1007/978-3-319-66182-7_86
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Shape Compactness for Segmentation

Abstract: We propose to constrain segmentation functionals with a dimensionless, unbiased and position-independent shape compactness prior, which we solve efficiently with an alternating direction method of multipliers (ADMM). Involving a squared sum of pairwise potentials, our prior results in a challenging high-order optimization problem, which involves dense (fully connected) graphs. We split the problem into a sequence of easier sub-problems, each performed efficiently at each iteration: (i) a sparse-matrix inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In these works, length is typically employed as a regularizer in the energy function. More complex regularizers have been demonstrated to further boost the performance of segmentation techniques, for example, convexity or compactness . Employing such regularizers may improve performance in the current application given the compact shape of the bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these works, length is typically employed as a regularizer in the energy function. More complex regularizers have been demonstrated to further boost the performance of segmentation techniques, for example, convexity or compactness . Employing such regularizers may improve performance in the current application given the compact shape of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…More complex regularizers have been demonstrated to further boost the performance of segmentation techniques, for example, convexity 65 or compactness. 66 Employing such regularizers may improve performance in the current application given the compact shape of the bladder. Furthermore, recent works have shown that combining several deep models can lead to important improvements in several segmentation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, and following recent works that interpret the output of the CNN as unary potentials in an energy minimization problem, we plan to further investigate the impact of different regularization terms in the esophagus segmentation performance. For example, a compactness term was recently proposed in, showing significant improvements of CNN segmentation results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our intuitive analysis with regards to some relationships between loss performance and dataset characteristics however, we admit to many limitations. For starters, the proposed benchmark can not be generic, as there are many existent prior-based losses that we fail to include: low-level prior 16,19,32 , high-level topological 33 or shape prior 17,20 . Moreover, due to the fact that high-level prior-based losses are customized to target a particular property, providing means of comparison with respect to their effectiveness is subjected to debate.…”
Section: Limitations Of the Current Proposed Benchmarkmentioning
confidence: 99%
“…18 Prior could also be high-level representing actual external medical information such as the shape of the organ, compactness or size, and are optimized directly based on ground-truth prior tags. 12,17,20 Over the past few years, prior-based losses, whether low-level or high-level, present a rising trend in today's research in semantic image segmentation, particularly in the medical field. Given the diversity of prior-based losses on different medical imaging challenges and tasks, it has become hard to identify what loss works best for which dataset.…”
Section: Introductionmentioning
confidence: 99%